Prevalence of rifampicin resistant mycobacterium tuberculosis and associated factors among presumptive tuberculosis patients in eastern Uttar Pradesh: a cross sectional study - Gautam, Praveen B.; Mishra, Ashwini; Kumar, Santosh (International Journal Of Community Medicine And Public Health, 2018)
Background: Drug resistant tuberculosis threatens global TB control and is a major public health problem in several countries and India has the highest tuberculosis in the world. The rifampicin resistance is a good predictor of multidrug resistant tuberculosis. The aim of this study was to determine the prevalence of rifampicin resistance M. tuberculosis and associated factor among presumptive tuberculosis patients in eastern Uttar Pradesh. Methods: A cross-sectional study was conducted from October 2016 to September 2017. Detection of M. tuberculosis and resistance to rifampicin was performed using Gene Xpert MTB/RIF assay. Data was collected using pre-structured questionnaire by face to face interview. The chi-square test was used to assess the statistical significance of each ratio, p<0.05 was considered significant. Results: Out of 510 patients, Mycobacterium tuberculosis was detected in 168 (32.9%). Out of these 168 patients, the prevalence of rifampicin resistance tuberculosis was 44 (26.1%). It was higher among male 38 (30.6%) than female 6 (13.6%). Regarding age distribution, maximum numbers of rifampicin resistance patients were in the age group of 20-40 years 36.7%. The prevalence of rifampicin resistance was 36 (27.6%) and 8 (21.0%) in pulmonary and extra-pulmonary respectively. Out of 44 rifampicin resistant cases, 39 (37.8%) were previously treated and 5 (7.6%) cases were treatment naïve patients. In this study, among presumptive DRTB cases, new 2 (11.7%), relapse 13 (39.3%), failure 23 (46.0%), loss to follow-up 1 (10.0%) and MDR contact 1 (20.0%) respectively were rifampicin resistant and one HIV seropositive patient was found to be rifampicin resistant. Conclusions: Previously treated cases were significantly associated with rifampicin resistance tuberculosis. The Gene Xpert is a good equipment for rapid detection and management of drug resistant tuberculosis for both pulmonary as well as extra-pulmonary tuberculosis.